REPRESENTATION OF HISTORICAL TRUTH IN 20TH-CENTURY UZBEK LITERATURE - Olimjon Dadaboev (Modern American Journals, 2025)
This article explores Oybek’s historical novel Navoi, which portrays the figure of Alisher Navoi not merely as an individual but as a symbolic representation of the Uzbek people’s cultural and spiritual renaissance in the 15th century. The study analyzes the artistic principles employed by the author in combining historical truth with fictional elements, thereby creating a realistic yet ideologically significant image of Navoi. Special attention is paid to the influence of Soviet-era ideological constraints, which shaped the depiction of Navoi as a humanist poet, a patron of the people, and a proponent of social harmony. The article also highlights scholarly views that emphasize the humanistic essence of Oybek’s conception of Navoi, underscoring the novel’s role in both reflecting and shaping national consciousness.
Keywords: Oybek, Alisher Navoi, historical novel, Uzbek literature, humanism, ideology, historical truth, fictional image, national consciousness.